Pemodelan Numerik Tsunami untuk Mengestimasi Waktu Tiba dan Ketinggian Maksimum Gelombang Tsunami di Teluk Amurang - Adelia Fatimah; Rigolda Djamaluddin; Suria Darwisito; Jane Marianne Mamuaja; Adnan Sjaltout Wantasen; Joshian Nicolas William Schaduw (Universitas Negeri Gorontalo, 2023)
Amurang Bay is a coastal area of South Minahasa Regency which is densely populated but faces the subduction zone of North Sulawesi which has the potential to generate earthquakes that trigger a tsunami. The process of the tsunami disaster occurred quickly, but the impact was very destructive and caused many casualties. This study aims to determine the propagation of tsunami waves with the worst scenario Mw 8.5 in Amurang Bay. Numerical methods in COMCOT software are used to model the propagation of tsunami waves in order to obtain an estimate of arrival time and maximum height of tsunami waves. Based on this modeling, the estimated arrival time of tsunami waves at the virtual tide gauge point in Amurang Bay is in the range of 8–11 minutes. The maximum height of tsunami waves is included in the alert category, which is 9.55 meters to 11.44 meters. The fastest estimated arrival time was recorded in Amurang Barat District and maximum height of tsunami waves was found in Tumpaan District. The results of this modeling can be used as one of the steps for mitigating tsunami disaster by preparing the surrounding community and assisting the evacuation process when a tsunami disaster occurs.